A high voltage direct current transmission system : natural and selective harmonic cancellation - Aziza Benaboud; Alfred Rufer (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
This study focused on the special High Voltage Direct Current technology. The context is given by combining two original solutions; the first solution, using a natural harmonic cancellation, consists to connect in series two classical frequency inverters which are coupled to the grid through a specific transformer connection.  On the other hand, the second solution is achieved by using three, five or more level converters in square wave modulation, in order to eliminate some selective harmonics by optimizing a switching angle. The simulation and experimental results indicate that the proposed High Voltage Direct Current transmission systems offer high efficiency, unity power factor and better current and voltage quality with fewer harmonic.